EE-MAC: Energy Efficient Hybrid MAC for WSN - B. Priya; S. Solai Manohar (International Journal of Distributed Sensor Networks, 2013)
A novel low power medium access protocol energy efficient MAC (EE-MAC) for wireless sensor network is proposed in this paper. EE-MAC targets for improving energy efficiency, delay performance and packet delivery ratio by considering various load conditions of the network. This protocol is based on the hybrid of TDMA and FDMA approaches. The novel idea behind EE-MAC is that it uses the priority concept with hybrid MAC scheduling in order to achieve its objectives. The performance of EE-MAC is obtained through simulations for various packet sizes, traffic loads, and different scenarios which show significant improvements in packet delivery ratio, energy efficiency, and delay compared to existing protocols.